"Hey everyone, look at me helping you!": A contingency view of the relationship between exhibitionism and peer-oriented helping behaviors. Issue 4 (November 2021) - De Clercq, Dirk; Pereira, Renato
This research investigates how an understudied personal resource (exhibitionism) might positively connect with peer-oriented helping behavior, as well as how this connection might be invigorated by four pertinent contextual resources: two resources that speak to beliefs about fair organizational treatment (informational justice and procedural justice) and two resources that capture how employees feel about their work functioning (job satisfaction and organizational commitment). Two-wave survey data collected among banking sector employees reveal that their desire to be the center of attention is associated with an enhanced propensity to extend help to other organizational peers, voluntarily. This process also is more likely when employees (1) believe that organizational authorities provide them with sufficient information, (2) perceive organizational procedures as fair, (3) feel happy with their current job situation, and (4) experience a strong emotional bond with their employer. JEL Classification:M50